Isolation of cDNA clones using yeast artificial chromosome probes. - Elvin, P (1990)
The cloning of large DNA fragments of hundreds of kilobases in Yeast artificial chromosomes, has simplified the analysis of regions of the genome previously cloned by cosmid walking. The mapping of expressed sequences within cosmid contigs has relied on the association of genes with sequence motifs defined by rare-cutting endonucleases, and the identification of sequence conservation between species. We reasoned that if the contribution of repetitive sequences to filter hybridizations could be minimised, then the use of large cloned DNAs as hybridisation probes to screen cDNA libraries would greatly simplify the characterisation of hitherto unidentified genes. In this paper we demonstrate the use of this approach by using a YAC, containing 180 kb of human genomic DNA including the aldose reductase gene, as a probe to isolate an aldose reductase cDNA from a lambda gt11 human foetal liver cDNA library.